The influence of delayed blastocyst development on the outcome of frozen-thawed transfer of euploid and untested embryos - Parnita Sardana; Jwal Banker; Reena Gupta; Aditi Kotdawala; P G. L. Lalitkumar; Manish BankerIntroduction (Wolters Kluwer Medknow Publications, 2020)
Objective: The primary objective is to compare live birth rates (LBRs) following frozen embryo transfer (FET) of euploid day 5 with day 6 blastocysts. We also compared LBRs following FET of untested blastocysts vitrified on day 5 and day 6 in self-oocyte and ovum donation (OD) cycles. Design: This was a retrospective observational study. Setting: Nova IVF Fertility, Ahmedabad. Materials and Methods: Ninety-seven FET using self-oocytes following preimplantation genetic testing A (PGT-A), 464 FET following OD, and 907 FET using self-oocytes without PGT-A testing between January 2016 and December 2017 were included in this study. Main Outcome Measures: LBR following FET in day 5 versus day 6 blastocysts in euploid embryos using self-oocytes and in untested embryos using both self and donor oocytes. Results: In PGT-A cycles, no statistically significant difference was observed in LBRs following transfer of euploid blastocysts developed on day 5 or day 6 (D5: 53%; D6:40%, P = 0.83). However, the LBRs with day 5 blastocysts were higher compared with day 6 group in untested group using both self and donor oocytes (self D5: 52.7%; D6: 38.2%; P = 0.001 and OD D5: 44.7%; D6: 29.8%; P = 0.001). Miscarriage rates were comparable in both the groups.Conclusions: The present study demonstrated comparable pregnancy outcomes following FET of euploid embryos vitrified on day 5 and day 6. However, higher LBRs were reported in day 5 group in untested embryos.